Adolescentes vítimas de violência sexual : crenças e valores relacionados à prevenção das doenças sexualmente transmissíveis e a AIDS - Silva, Kelanne Lima da (2011)
Sexual assault is characterized as a serious public health problem that leads to disorders in the bio-psychosocial and sexual development of the victims, especially when the aggression happens in adolescence, because these subjects are in a stage of life marked by changes and adaptations, especially concerning sexuality. Therefore, the values and beliefs of the victims of sexual assault must be understood to promote the adoption of a healthy sexual behavior. It was aimed to understand how beliefs and values of adolescent victims of sexual assault influence the behavior of prevention of STD/AIDS based on the Health Belief Model. It is a qualitative descriptive research carried out at a Host Institution in the City of Fortaleza from May to July 2011 with eight adolescent victims of sexual assault. Using as tools and procedures for data collection: participant observation of all meetings, which were registered in a field diary; all the material produced during the focus groups, such as posters, drawings, among others; and the transcription of the dialogue recording during the group strategies and semi-structured interviews. The information was organized according to the Health Belief Model dimensions. All legal and ethical aspects of researches involving human beings were respected. Initially, it was necessary to characterize the study participants and it was found that the life stories of these adolescents were consistent with the literature. Regarding the categories created according to the Health Belief Model: the adolescents lack knowledge about these diseases and don't considered them susceptible to STD/AIDS because they believe that they will not relate sexually with men, in spite identifying the greater vulnerability of women to such pathologies; concerning the perception of gravity, they classified these diseases as serious, incurable, and that changes social life, demonstrating fear of contracting these diseases; they identified as benefits and barriers of preventive method: it is easy to access and use, and prevents both diseases as pregnancy, but interferes with sexual pleasure; and its use is related to cultural and social issues, we also emphasize that the abuse of alcohol and drugs interferes in the adoption of healthy behaviors. We conclude that the beliefs and values of these adolescents make them vulnerable to STD/AIDS, being necessary to reflect on the consequences of sexual violence in their lives to build strategies and preventive actions aimed at this target audience in terms of a safe development of sexuality, minimizing trauma and suffering resulting from this experience in their lives, making them aware of their sexual and reproductive rights.